The hosts of "Ribatat Al- Ilm ", in Morocco and Andalusia between the 8th and the 10 century (Hijri) - serhani, Belkhir (Journal of Humanities & Social Sciences, 2020)
The study purpose was to show the most important conditions that the "Waqf" donators had put to "Tahbiss" (to donate their goods, whether giving their property or lands for the sake of education), and also to state the attitude of the Muslim western Faqihs (experts in the Islamic law) towards the conditions set before. The inductive syllabus was used to prove that the faqihs were giving very important consideration and caring to the Waqf in the educational instructions throughout a good governance of the resources and respecting the conditions of people of donate and give their goods the waqf people. Finnaly, Many recommendations and suggestions were set forth to organize the waqf in the Islamic institutions in order to preserve its resources for a good performance.